2012
DOI: 10.1188/12.onf.468-477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Fatigue, Sleep, and Performance: A Randomized Trial

Abstract: Exercise is safe and has physiologic benefits for patients undergoing MM treatment; exercise combined with epoetin alfa helped alleviate anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 49 publications
2
82
0
1
Order By: Relevance
“…38,40 Patients with haematological malignancies can experience many complications during treatment, including muscle atrophy, cachexia, anaemia, physical deconditioning and psychological distress. 64,108,109 In particular, anaemia has been shown to affect people with haematological cancers more than those with solid tumours 110 and this is a known contributor to cancer-related fatigue. 27 Therefore, this complication may be less able to be resolved through exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,40 Patients with haematological malignancies can experience many complications during treatment, including muscle atrophy, cachexia, anaemia, physical deconditioning and psychological distress. 64,108,109 In particular, anaemia has been shown to affect people with haematological cancers more than those with solid tumours 110 and this is a known contributor to cancer-related fatigue. 27 Therefore, this complication may be less able to be resolved through exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of participants were female (70%), with a mean age of 55 years (SD 9) and a mean body mass index of 27 kg/m 2 . Solid tumours were investigated in 34 trials (81%), haematological cancers were investigated in four trials, [63][64][65][66] with an additional four trials investigating a combination of solid and haematological cancers. [67][68][69][70] Breast cancer was the most frequently reported (27 trials, 64%), 30,60-62,68-94 followed by prostate cancer (14 trials, 24%).…”
Section: Participantsmentioning
confidence: 99%
“…To our knowledge, only one behavioral intervention study has been conducted in HCT recipients with the primary aim of improving sleep disruption outside the context of a diagnosed sleep disorder (65). In addition, five behavioral intervention studies have examined sleep disruption as a secondary outcome (66-70).…”
Section: Treatment Of Sleep Disruption and Disordersmentioning
confidence: 99%
“…All six studies were randomized trials of psychoeducation, stress management, aerobic exercise, and resistance training alone or in combination during the inpatient period; one study also followed patients for six months post-HCT (66). Samples consisted of patients receiving allogeneic HCT (67, 69) autologous HCT (70), tandem autologous HCT (65), and either allogeneic or autologous HCT (66, 67). All reported null results for sleep disruption compared to usual care.…”
Section: Treatment Of Sleep Disruption and Disordersmentioning
confidence: 99%
“…The observed impairments of physical function suggest that interventions designed to augment VO 2peak and functional capacity in survivors of MM warrant study. Initial work by Coleman et al 35,36 found that a program of home-based gentle stretching and aerobic exercise reduced the requirement for red blood cell transfusion in patients with MM undergoing ASCT, although no effects on PROs were seen. Groeneveldt et al 37 reported that supervised aerobic and resistance training was safe and feasible and was associated with improvements in QOL and fatigue in 37 survivors of MM.…”
Section: Discussionmentioning
confidence: 98%